(untitled) (Journal of the College of Basic Education, 2022)
The research aims to identify the spatial variation of non-vegetation agricultural tenure in Wasit GovernorateAnd knowing the reasons for that discrepancy. The research began by defining the importance of livestock as it has a roleAl-Ranisi contributes to the prosperity of the economy, just as animal husbandry increases employment opportunities for women and childrenAgricultural tenure and identification of sheep varieties such as Iraqi, Kurdish and Awassi. The research also dealt withGoats and their geographical distribution in Wasit Governorate, and the difficulties they suffered from, such as diseases and wasteland of pasturesAnd high prices. As for buffaloes, they are spread in the swampy area of ​​the study area and near streamsRivers. As for camels, their geographical distribution is different, as the districts of Jassan and Sheikh Saad ranked first.